2009
DOI: 10.1021/es900941w
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of PCB Contamination in an Arctic Coastal Environment: A First Step in Assessing Ecosystem Recovery after the Removal of a Point Source

Abstract: Studies have documented the presence of organic contaminants in Arctic marine environments due to local point sources, but little long-term data is known of the recovery process once those contaminants are removed. In this study, natural recovery of a local marine food web from a historic terrestrial source of polychlorinated biphenyls (PCBs) at Saglek Bay is examined. PCBs were measured in marine sediments, shorthorn sculpin (Myoxocephalus scorpius), and black guillemots (Cepphus grylle) to assess ecosystem r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Whereas concern regarding the long-range transport of PCBs to the Arctic has been the focus of a number of studies (Macdonald et al, 2000; Wania, 2003), the influence of local point sources, such as the large number of sites associated with the Distant Early Warning (DEW) line in Canada, and formerly used defense sites (FUDS) in Alaska, is of continuing concern to residents who live in close proximity to those sites (Ap O’Hehir et al, 2005), many of whom rely on wildlife for subsistence. While a great deal of effort has been directed towards remediation of several DEW and FUDS contaminated sites (Poland et al, 2001; Stow et al, 2005), with clean-up efforts resulting in lower exposures of PCBs (Brown et al, 2009), sites that remain contaminated continue to influence PCB levels in wildlife (Anthony et al, 2007; Ricca et al, 2008; Miles et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Whereas concern regarding the long-range transport of PCBs to the Arctic has been the focus of a number of studies (Macdonald et al, 2000; Wania, 2003), the influence of local point sources, such as the large number of sites associated with the Distant Early Warning (DEW) line in Canada, and formerly used defense sites (FUDS) in Alaska, is of continuing concern to residents who live in close proximity to those sites (Ap O’Hehir et al, 2005), many of whom rely on wildlife for subsistence. While a great deal of effort has been directed towards remediation of several DEW and FUDS contaminated sites (Poland et al, 2001; Stow et al, 2005), with clean-up efforts resulting in lower exposures of PCBs (Brown et al, 2009), sites that remain contaminated continue to influence PCB levels in wildlife (Anthony et al, 2007; Ricca et al, 2008; Miles et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Waste handling in the form of sewage lagoons, dumpsites at military installations and solid waste dumps in small communities and industrial installations (i.e., oil-drilling sumps) continues to the present . Waste disposal in landfills and dumpsites is a potential local source of POPs and has received significant attention in the case of PCBs associated with the distant early warning sites ("DEW-line") across Arctic Canada (e.g., Brown et al, 2009). Recently, PBDEs have been measured in soils around dumpsites in Cambridge Bay and Iqaluit in Arctic Canada.…”
Section: Mobilization Of Contaminants Due To Thawing Permafrostmentioning
confidence: 99%
“…Black guillemot eggs were collected from 14 of the 54 nest (Fig. 1) [8,11]. The mean black guillemot nestling liver and egg PCB concentrations for each group are presented in Table 1.…”
Section: Exposure Characterizationmentioning
confidence: 99%
“…The final management decision, after consultation with a broad stakeholder group including government regulators and the Labrador Inuit Association (now the Nunatsiavut Government), was to allow natural recovery to occur while conducting monitoring to ensure that this process occurred as expected [3,4]. A followup study [8] demonstrated that natural ecosystem recovery was indeed occurring and that, as of 2006, the PCB concentrations in the sediments near the former source were rapidly approaching the site-specific threshold for ecological risk (77 ng/g dry wt). Companion studies also have shown that the declines in PCB concentration in the sediments are associated with decreases in biological effects (manuscripts in preparation).…”
Section: Implications For Sediment Managementmentioning
confidence: 99%
See 1 more Smart Citation